Revolution within the revolution : cotton textile workers and the Mexican labor regime, 1910-1923 - Bortz, Jeff (Stanford University Press, 2008)
Mexico's 1910 revolution ushered in a revolutionary era: during the 20th century, Mexican, Russian, Chinese, Cuban, Nicaraguan, and Iranian revolutions shaped local, regional, and world history. Because Mexico was at the time a rural and agrarian country, it is not surprising that historians have concentrated on the revolution in the countryside, where the rural underclass fought for land. This book uncovers a previously unknown workers' revolution within the broader revolution. Working in Mexico's largest factory industry, cotton textile operatives fought their own fight, one that challenged and overthrew the old labour regime and changed the social relations of work.